PENGUKURAN KINERJA DENGAN MENGGUNAKAN METODE BALANCED SCORECARD ( Studi Kasus pada RSUD RAA Soewondo Pati ) - Martono, Martono; Nusantara, Agung (Jurnal Ilmiah Telaah Manajemen, 2016)
Each busines unit is required to improve the quality of and work more affectively and aficiently in order to obtain optimal result that still exist in the world of busines. Change the orientation from product of oriented become customer oriented requires management to look at organization in a comprehensively. Performance assesments in RSUD RAA Soewondo Pati has been carried out only on some components just like the analysis of financial performance and service performance as measured by the method of performance reports. Measurement of performance with balanced Scorecard is a comprehensive performance measurement and is a suitable alternative performance measurement for hospital. Keywords : Balanced Scorecard, Customer Perspective, Financial Perspective, Learning and Growing Perspective